N.F.S. Grundtvig : as a political thinker - Korsgaard, Ove (DJØF Publishing, 2014)
N.F.S. Grundtvig remains the most cited person in political debates in Denmark for the last 150 years. Even though Grundtvig is not that well-known internationally as a political thinker (his educational writings have attracted far greater attention), he is rightly regarded as the single individual who has had the greatest importance in the formation of the Danish nation. This book presents a biography of Grundtvig and an analysis of his contribution to political science. The author scrutinizes the life and thoughts of democracy, equality and the people of Grundtvig and thus how his notion of f.